Study the effect of Lactobacillus plantarum ATCC 14917 for caries prevention and anti-obesity - Yang, Wei; Jiang, Mingxin; Chen, Bairu; Jiang, Kongzhao; Ma, Nan; Li, Yimin; Wang, Meng; Bao, Meihua; Wang, Chengyue; Yang, Xiaopeng (Frontiers in Nutrition, 2024)
IntroductionA complicated scenario where “multiple disease threats coexist and multiple health influencing factors are intertwined” is demonstrated by the fact that dental caries, obesity myopia and scoliosis have emerged as global public health issues. The problem of diseases co-existing in living things can be resolved by using probiotics. Lactobacillus plantarum, has gained attention recently due to its probiotic properties, useful traits, and potential medical applications.ObjectiveExamining the anti-obesity and anti-caries effects of L. plantarum ATCC 14917 on dental caries and obese rat models caused by a high-fat and high-sugar diet is the aim of this study.MethodIn vitro, we assessed the L. plantarum strain’s probiotic properties, such as its antibacterial activity and ability to build biofilms, to determine its ability to inhibit Streptococcus mutans. Prior to the in vivo experiment, the subsist test for L. plantarum ATCC 14917 was carried out by mimicking its capacity to lower blood sugar and blood lipid levels as well as its tolerance to gastrointestinal disorders. In order to assess the health promotion effect of L. plantarum in vivo. Three-week-old rats were fed a high-sugar, high-fat diet for 8 weeks. They were split into three groups: the control group (Control), the caries and obesity group (CA _OB) and the caries and obesity treated with L. plantarum ATCC14917 group (LP). L. plantarum ATCC 14917 was applied during the experiment, and the associated indices were then thoroughly assessed. These included the use of Mirco-CT to calculate the enamel volume, the staining of liver and fat cell sections, serological analysis, and 16S rRNA sequencing of feces.ResultsIt was proved that the L. plantarum could inhibit the proliferation of S. mutans and remove dental plaque biofilm in time, which showed the remarkable effects of anti-caries in vitro. The demineralization rate of enamel decreased by 44.10% due to the inhibition of acid production by pathogenic bacteria. Moreover, In intestinal and stomach juice simulations, L. plantarum has a high survival rate. The characteristics of bacterial activity in a wide range of pH could degrade triglycerides and glucose in vitro smoothly. The LP group demonstrated it by reducing animal weight, serum biochemical indices, and HE-stained adipocytes as compared to the CA_OB group. 16S rRNA sequencing data showed that a high-fat and high-sugar diet induced the imbalance of intestinal flora, which showed an increase in microbial abundance, including unclassified_o__Clostridia_UCG-014, unclassified_f__Oscillospiraceae, Turicibacter, unclassified_f__Lachnospiraceae, Clostridium_sensu_stricto_1. After the intervention of L. plantarum, the number of Lactobacillus, Limosilactobacillus, unclassified_f__Muribaculaceae, Blautia, Faecalibaculum increased significantly.ConclusionTherefore, L. plantarum ATCC 14917 performed the potential of reducing tooth decay and controlling weight gain by a single strain. Support the management of dental caries and obesity, and establish a foundation for future functional food research and development.